Fundamentals of government budgeting in India - Ganguly, S. P. (New Delhi, 1993)
This book indicates the procedure for preparation of Government budgets in India, constitutional provisions relating to Government budgeting and the roles of Finance Commission and Planning Commission in the matter.
Keywords: Public administration; IAAS as an author; Indian Audit and Accounts Service